Common Complications of Cesarean Section During the Year 2017 in King Abdulaziz Medical City, Jeddah, Saudi Arabia - Aljohani, Aljoharah A (Cureus, 2021)
Cesarean section (CS) is one of the most well-known major obstetrics surgeries and one of the oldest operations in the area of abdominal surgery. It is used for the purpose of delivering the newborn and the placenta through the abdominal wall incision (laparotomy) as well as Uterine incision (hysterotomy), followed by suture of the uterus and abdominal wall layers. Most common maternal complications internationally, according to literature were bleeding and wound infection. Most common fetal complications according to the literature were depressed Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score, low blood pH and ICU admissions. The aim of this study is to determine the most common CS complications among all the deliveries at King Abdulaziz Medical City (KAMC) in Jeddah in 2017 and to estimate maternal and fetal complication rates following CS. Comparing the rate of complication between residents and non-residents physicians performing a CS was tested as a secondary outcome. To the best of our knowledge, this is a novel research in this medical center at KAMC Jeddah that will aid in quality improvement in both clinical services and training activities of residents. The maternal and fetal complication rates were assessed in a cross-sectional chart review study. In order for this method to be achieved, a secondary data collection sheet was constructed to collect all eligible patient health records. This literature review was based on estimating the rate of CS complications for the mothers and their neonates that founded approximately 7% and 6%, respectively, where the procedure was either performed electively or emergently within the period of 1 January to 31 December 2017. Also, all patients with medical and surgical conditions were included while intrauterine fetal death was excluded. The most common maternal complications documented in our population were bleeding and wound extension, while the most common fetal complications were low APGAR score and NICU admissions. No statistical significance was found in either complications in terms of the correlation between demographical factors, maternal health conditions and gravida status. As for the secondary objective, the association between operator level of training and rate of complications revealed a higher percentage rate of maternal and fetal complications among consultants, which were 6.2% and 8.2%, respectively, mainly because the number and complexity of their cases in comparison to cases held by residents and others.